Cranial Material of Long-Snouted Dolphins (Cetacea, Odontoceti, Eurhinodelphinidae) from the Early Miocene of Rosignano Monferrato, Piedmont (NW Italy): Anatomy, Paleoneurology, Phylogenetic Relationships and Paleobiogeography - Vera Tosetto; Piero Damarco; Riccardo Daniello; Marco Pavia; Giorgio Carnevale; Michelangelo Bisconti (Diversity, 2023)
We provide a new study of previously published eurhinodelphinid materials from the early Miocene of Piedmont (NW Italy) based on a new preparation of the fossil specimens. We studied specimens previously assigned to Tursiops miocaenus and Dalpiazella sp. and provide new anatomical data on the eurhinodelphinid skull and ear bones. In particular, we suggest that a skull that was previously assigned to Tursiops miocaenus must be reassigned to Ziphiodelphis sigmoideus (Cetacea, Odontoceti, Eurhinodelphinidae) based on new comparisons of the squamosal. This finding enabled us to provide new anatomical information on the ear bone anatomy of Z. sigmoideus that was previously unknown. The material originally assigned to Tursiops miocaenus is currently lost. For this reason and due to the fact that the partial illustration of this species by Portis does not allow us to find diagnostic characters for this species, we decided that Tursiops miocaenus is a nomen dubium. Analysis of additional isolated teeth previously assigned to Tursiops miocaenus led to the conclusion that these specimens represent Odontoceti incertae sedis. We performed a new phylogenetic analysis by adding newly discovered character states to a previous dataset and a paleobiogeographic analysis of Eurhinodelphinidae. We found two monophyletic clades within this family. The paleobiogeographic pattern found by the present work suggests the existence of North Atlantic and Mediterranean clades with some species distributed among both basins. We analyzed the virtual endocast of Ziphiodelphis sigmoideus and found that it resembles that of Schizodelphis in several respects, suggesting that some of the more derived characters of the odontocete brain were still absent in these early Miocene eurhinodelphinids.